PENERAPAN TERAPI HIPNOSIS LIMA JARI TERHADAP ANSIETAS PASIEN HIPERTENSI DI RUMAH SAKIT HARAPAN BUNDA KOTA BATAM - Tasya Indri Pratiwi; T Eltrikanawati T Eltrikanawati (Ensiklopedia of Journal, 2025)
Hypertension is defined as an increase in systolic blood pressure of at least 140 mmHg or diastolic blood pressure of at least 90 mmHg. Based on data from the World Health Organization (WHO), it is estimated that 1.28 billion adults aged 30-79 years worldwide suffer from hypertension. The highest proportion of high blood pressure in the Riau Islands Province is Karimun Regency at 30.3% and the lowest is Batam City at 15.7%. This professional scientific paper aims to provide nursing care to Mr. T by applying five finger hypnosis therapy to anxiety in hypertensive patients at Harapan Bunda Hospital. The method used in this Professional Scientific Writing work is a case study based on the stages of nursing care including assessment, diagnosis, intervention, implementation and nursing evaluation. The results showed that there was a decrease in anxiety levels from the first day, with an Anxiety Score of 21 (Moderate Anxiety) and on the third day the anxiety score decreased to 13 (no anxiety), as well as decreased anxiety and decreased tension in accordance with the expected goals and criteriaKeywords: Hypertension, Nursing Care, Five finger hypnosis